QUALITY OF CITY PARKS AS A PUBLIC GREEN OPEN SPACE BANDA ACEH CITY: KUALITAS TAMAN KOTA SEBAGAI RUANG TERBUKA HIJAU PUBLIK KOTA BANDA ACEH - Desyan Ria; Edi Saputra; Eka Rahmi; Reza Fahmi (ROCE : Jurnal Pertanian Terapan, 2025)
City parks are part of public green open space in urban areas, the city of Banda Aceh already has several locations that have been used as city parks. The purpose and function of city parks are regulated in Law No. 26 of 2007 concerning RTRW. This research was conducted at five city park locations, namely Taman Sari & Kids Rock, Tsunami Education Park, Lambung Park, Meuraxa Tourism Park, and Pantai Cermin Park. Visitors to city parks in the city of Banda Aceh are mostly students and families with an average age of 19-15 and 25-35. The community utilizes the physical function of the Banda Aceh city park as a place of relaxation, recreation, a place for children to play, and a place to exercise, while its social function is as a place to interact with residents. The quality of city parks in Banda Aceh in terms of area is sufficient, and public facilities are widely available.